Cesarean Section Due to Social Factors Affects Children's Psychology and Behavior: A Retrospective Cohort Study - Shi, Xiu-Yu; Wang, Jing; Zhang, Wei-Na; Zhao, Meng; Ju, Jun; Li, Xiao-Yan; Lu, Qian; Wang, Bin; Zou, Li-Ping (Frontiers in Pediatrics, 2021)
Background: Caesarean section (CS) use has reached a frequency well above what is expected on the basis of obstetric indications. In China, a significant proportion of women undergo CS because of social factors, which provides a good model to study whether non fetal triggered delivery will affect children’s behavior. Thus, we assessed the impact of CS due to social factors on child psychology and behavior. Methods: We conducted a retrospective cohort study. Children were divided into three groups according to delivery mode: vaginal delivery (VD), CS with medical indications, and CS due to social factors (also called as elective caesarean section, ECS). Parents or guardians were required to complete four rating scales of Chinese version (Conners’ Parent Rating Scale (CPRS), Child Behavior Checklist-Parent Form (CBCL-PF), Swanson, Nolan, and Pelham rating scale-Parent Form (SNAP-IV-PF), and Behavior Rating Inventory of Executive Function-Parent Form (BRIEF-PF)) on psychological and behavioral problems regarding their children. Results: Among the 38,780 children aged 7 to 15 years, 29,103 (75.05%) were delivered by VD and 9,677 (24.95%) were delivered by CS (7,844 with medical indications; 1,833 by ECS). Ten covariates were found to significantly affect ECS. Four rating scales were used in this study: CPRS, CBCL-PF, SNAP-IV-PF, and BRIEF-PF. ECS affected child psychology and behavior in several aspects including inattention, hyperactivity/impulsivity, social problems, and executive dysfunction. Regarding to inattention, the ECS group had a higher SNAP-IV-PF inattention score (P=0.03), compared with the VD group. Logistic multivariate stepwise regression analysis showed that in the ECS group, the ORs were 1.20 in the partially adjusted analyses of SNAP-IV-PF and CPRS. Regarding to social problems, ECS group had a higher CBCL-PF score for the social problems category compared with the VD group (P=0.0001). Kruskal–Wallis rank sum tests showed that the ECS group had higher BRIEF-PF scores regarding Working Memory (P=0.04), and Organize (P=0.01) compared with the VD group. Conclusions: Caesarean section affected the offspring’s psychology and behavior. After removing possible influence of medical indications, the effect of CS due to social factors on the offspring’s psychology and behavior still exists